Development of an integrated modeling platform for watershed simulation. (May 2021) - Nguyen, Van Thinh; Nguyen, Hong Ha; Han, Gidon
Abstract: The main objective of this study is to develop a new modeling platform, which integrates all necessary modeling components for watershed simulation, including a pre-processing tool, a coupling of hydrologic and river transport models, and a calibration and uncertainty analysis tool. All components are connected and immersed into an open source non-proprietary GIS software. The modeling platform is programmed in Microsoft Visual Studio (VB.Net), and equipped with a built-in GUI facility. A minimum data input requirement, full capabilities and potential applicability are most compelling of this modeling platform. The modeling platform was applied to different watersheds under distinguished weather conditions; the simulation results show not only a good agreement with the observation data, but also some improvements in comparison with the results obtained from other prevalent hydrologic models. The Highlights of our study are: A new integrated modeling platform is developed for watershed modeling. Minimum data input requirement is appealing of this simulation tool. The simulation tool is included full facilities of watershed modeling. The simulation results show a very good agreement with observation data.